English Language Proficiency and Individual Ecomonic Enhancement - Juliandi Sahputra (Madani: Jurnal Ilmiah Multidisiplin, 2023)
English as one of the international languages has many benefits that can be felt by its users both from a social and economic perspective. This study aims to dig up information about the effect of English language skills on the economic level of the family using the literature review or literature review method. The results of this study explain that being able to work in a multinational/international company and several elite agencies can have an impact on improving a person's economy and society. It's just that one of the requirements that someone must have to get in these companies is to have the ability to speak English both orally and in writing.